Catalytic oxidation mechanism of NO to HNO3 on TiO2 (101) and (001) surfaces and the influence factors on NO removal: A DFT study. Issue 1 (February 2021) - Wang, Zehua; Lv, Guochun; Zhang, Chenxi; Sun, Xiaomin
Graphical abstract: Highlights: A DFT study is employed to calculate the catalytic oxidation of NO in this paper. The removal of NO to HNO3 is easier to occur on the TiO2 (001) than (101). The additional NO molecule can improve the formation of HONO not HNO3 . Additional NO effectively reduce the barrier energy in oxidation of NO and O2 . Trans-ONONO2 preferentially generates than NO2 in the presence of additional NO. Abstract: Theoretical study on the selective catalytic oxidation of NO to form HNO3 on the different TiO2 (001) and (101) surfaces was performed by DFT calculations. The addition of additional NO molecules to the oxidation process also is discussed. The result shows that HNO3 is more easy to generate on (001) than (101) surface. The adsorbed H atom on surface is beneficial for the transformation of O2 to the superoxide radical (O2 ·− ) that has a favorable role for the oxidation of NO on surface. In addition, it is manifestly demonstrated that the participation of the additional NO in the reaction of NO and O2 not only modifies the known NO oxidation pathway ( N O → N O 2 → H N O 3 ), but also affects the existence of the product HNO3 . The trans-ONONO2 can firstly be formed if the additional NO molecule involves in the oxidation reaction in the beginning. When the additional NO molecule encounter with the precursor (H···NO3 ) of oxidation product (HNO3 ), it can improve the formation of HONO not HNO3 . This study gains more insight into the mechanism of NO oxidation and has a potential atmospheric importance.